The Level of Humanin, a Mitochondrial Peptide is Higher in Breast Cancer Patients - Hekim, Munevver Gizem; Bulut, Ferah; Ozgen, Aslisah; Yildirim, Nilgun; Yur, Mesut; Ozcan, Sibel (Wiley, 2023)
[Abstract Not Available]
Keywords: Humanin; Mitochondrial Dysfunction; Breast Cancer